The influence of covid-19 on industrial work practices of building engineering students in vocational school - Jonni Mardizal; Rezo Haristama Narwansyah; Palmizal Palmizal; Samsudin Samsudin (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This research was conducted to determine the magnitude of the influence of COVID-19 on the implementation of Industrial Work Practices for Building Engineering students of SMKN 1 West Sumatra. This research includes quantitative research of associative approaches. The population of this study was students of class XI Building Engineering, which numbered 50 students. Data collection is carried out using questionnaires. Questionnaires are used to measure COVID-19 variables and Industrial Work Practices. Instrument testing was carried out at SMKN 1 West Sumatra in class XI students of the Mechatronics Expertise Program, totaling 30 students. The data analysis techniques used are the prerequisite analysis tests, namely the normality test and linearity test, and the hypothesis test used is a simple regression analysis. The results of the research showed that there was a positive and significant influence of COVID-19 on the implementation of Industrial Work Practices for Building Engineering Students of SMKN 1 West Sumatra. This research indicates possible changes in building engineering education methods and emphasizes the importance of flexible skills in response to changing industrial work practices.